2012
DOI: 10.1007/s10157-012-0671-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dialysis in peritoneal dialysis: utility of bioimpedance to calculate Kt/V and the search for a target Kt

Abstract: BIS is a simple, applicable technique for calculating V in dialysis that can be especially useful in PD patients compared with the anthropometric formulas, by the abnormally distributed body water in these patients. Other parameters obtained by BIS will serve to assess both the distribution of body volume and nutritional status in the clinical setting. The target Kt value obtained from Kt/V bis allowed us to measure the efficacy of PD in a practical way, omitting V measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…While some studies also used other methods to measure Volume of distribution like Bioimpedence method. 11 …”
Section: Discussionmentioning
confidence: 99%
“…While some studies also used other methods to measure Volume of distribution like Bioimpedence method. 11 …”
Section: Discussionmentioning
confidence: 99%
“…We proceeded to the recording of impedance, resistance, reactance, and phase angles and the subsequent transformation into estimates of lean body mass, body fat, cell mass, total body water, and intracellular water. [23,24]…”
Section: Methodsmentioning
confidence: 99%
“…Assuming that this compartment generates uremic toxins, dialysis dose should be proportionally higher in small patients . Corroborating this, several studies assessed outcomes with Kt alone as dose index and found a more straightforward relationship to odds of death than with Kt/V . However, several of the characteristics associated with lower Kt are by themselves related to risk, such as age, central vein catheters or inadequate dialyzer blood flow (corresponding to access problems and dismal vascular status) …”
Section: Invalidity Of Kt/v In Specific Populationsmentioning
confidence: 99%
“…The definition of V, inherent to the continuous nature of PD, relies on anthropometric formulae. When Kt is normalized to other indices of body mass, subgroup analyses have pointed out discrepancies in adequacy that were not unraveled by considerations of classical Kt/V . Thus, estimating urea distribution in PD is subject to significant error …”
Section: Invalidity Of Kt/v With Specific Dialysis Strategiesmentioning
confidence: 99%